Role of School Employees' Mental Health Knowledge in Interdisciplinary Collaborations to Support the Academic Success of Students Experiencing Mental Health Distress. Issue 2 (16th February 2017) - Frauenholtz, Susan; Mendenhall, Amy N.; Moon, Jungrim
Abstract: Children with mental health disorders are at elevated risk of deleterious academic outcomes. The school, acting as a bridge between home and community, is a key site for identification and intervention with children experiencing mental health distress. Yet survey research has indicated that many teachers and other school staff have limited knowledge of children's mental health and are unprepared to support students in distress. Grounded in collaboration theory, the current study extends previous research by conducting focus groups with both school staff and community mental health center professionals to deepen understanding of how school employees' knowledge of children's mental health influences their ability to recognize and collaboratively support students in distress. Results revealed that many school staff experience challenges in supporting students because of their limited mental health knowledge, particularly in the areas of symptom identification, psychotropic medication, and community mental health services. The identified lack of children's mental health knowledge also contributes to the existence of mental health stigma. In addition, group participants identified training about children's mental health and support from upper-level administration as key needs to increase knowledge and better support students' emotional and educational well-being. The article concludes with a discussion of the implications and recommendations for school social workers.